Radiographic evaluation of the curvature degree and radius in the mesiobuccal canals of maxillary first molars - Burbano Balseca, María José (2018)
Objective: Determining the curvature degree and radius and its root canals association in mesial roots of human maxillary molars of Ecuadorian population.Materials and methods: A total of 50 human maxillary first molars extracted were studied which were obtained from the Tumbaco health sub-center’s teeth bank, Pichincha Ecuador, facts as teeth with a previous root canal treatment, cavities, root resorptionand fracture were the exclusion criteria. Periapical films withparalleling technique were taken; the curvature degree was measured mesio-distally with the Schneider 1971 technique and the curvature radius was obtained with the technique described by Estrela 2008. The data collected were analyzed with the Mann Whitney’s U Test with significance level of 5%. Results:The curvature angle was determined as 10%, 58% and 32% for low, moderate and severe respectively;and the curvature radius was 64%, 34% and 2% for mild, moderate and severe respectively. Among the groups studied, there was a statistically significant difference between the moderate angle and the mild radius (p=0,02). Conclusion: The study found that the moderate curvature angle and mild radiusare the most frequent.